Improving Concrete Durability by Using Optimized Aggregate Gradation and Reducing Cement Content - Chung, Hung-Wen; Subgranon, Thanachart; Tia, Mang (Proceedings of the International Conference on Civil Infrastructure and Construction (CIC), 2020)
This study evaluated the effects of (1) reducing the cementitious content, (2) the use of optimized aggregate gradation (OAG) technique, and (3) the use of Portland limestone cement (Type IL) in Florida Class I pavement and Class IV structural concrete. The potential performance of the pavement concrete mixes was also evaluated using critical stress analysis using a 3D FEM model. The compressive strength, modulus of rupture, modulus of elasticity, Poisson’s ratio, splitting tensile strength, coefficient of thermal expansion, rapid chloride permeability, and surface resistivity of the concrete mixes using normal Portland cement (Type I/II) and the concrete mixes using Type IL cement were similar to one another. The results of critical stress analysis indicated that the pavement concrete using Type IL cement had a predicted performance similar to concrete using Type I/II cement. The predicted performance of the pavement concrete was improved when the OAG technique was used. The main findings from this study are as follows: (1) The cementitious content of typical Florida pavement and structural concrete can be reduced by as much as 10 to 15% without loss in workability of the fresh concrete, and without decreasing the strength and durability of the hardened concrete. (2) Portlandlimestone cement (Type IL) can be used as a substitute for ordinary Portland cement (Type I/II). (3) The OAG technique can be used to efficiently reduce the cementitious content of the concrete mixes and to improve their performance.